Molecular cleft or tweezer compounds derived from trioxabicyclo[3.3.1]nonadiene diisocyanate and diacid dichloride - Kollenz, Gert; Smounig, Ralf; Belaj, Ferdinand; Kvaskoff, David; Wentrup, Curt (Beilstein Journal of Organic Chemistry, 2015)
The structures of two derivatives of the bisdioxine diisocyanate 1, the bisurea 4 and the biscarbamate 5, are established by X-ray crystallography and DFT calculations. These compounds possess endo,endo structures, in the case of the bisurea 4 with two nearly parallel pendant chains. The X-ray structures are reproduced very well by DFT calculations. Similar endo,endo conformations are calculated for the bisamide crown ether derivatives 7, where two proximate and nearly parallel crown ether units endow the molecules with a claw-like molecular cleft or tweezer structure as evidenced by an enhanced ability to extract some alkali, alkaline earth and rare earth metal ions.
Keywords: carbamates; crown ethers; diisocyanate; isocyanate; ureas

(untitled) - Smounig, R.; Leber, S.; Kvaskoff, D.; Kollenz, G.; Wentrup, C. (RSC Adv., 2012)

(untitled) - Kappe, C. O.; Kollenz, G.; Fabian, W. M. F.; Wentrup, C.; Färber, G. (J. Org. Chem., 1993)

(untitled) - Kremsner, J.; Wallfisch, B. C.; Belaj, F.; Uray, G.; Kappe, C. O.; Wentrup, C.; Kollenz, G. (Eur. J. Org. Chem., 2008)

(untitled) - Chen, C. W.; Whitlock, H. W., Jr (J. Am. Chem. Soc., 1978)

(untitled) - Rebek, J., Jr; Marshall, L.; Wolak, R.; McManis, J. (J. Am. Chem. Soc., 1984)

(untitled) - Rebek, J., Jr; Askew, B.; Killoran, M.; Nemeth, D.; Lin, F. T. (J. Am. Chem. Soc., 1987)

(untitled) - Rebek, J., Jr (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Zimmerman, S. C. (Top. Curr. Chem., 1993)

(untitled) - Harmata, M. (Acc. Chem. Res., 2004)

(untitled) - Klärner, F.-G.; Schrader, G. (Acc. Chem. Res., 2013)

(untitled) - Smounig, R.; Kappe, C. O.; Wentrup, C.; Kollenz, G. (Monatsh. Chem., 2003)

(untitled) - Smounig, R. (Karl Franzens Universität Graz, 1998)

(untitled) - Heilmayer, W.; Smounig, R.; Gruber, K.; Fabian, W. M. F.; Reidlinger, C.; Kappe, C. O.; Wentrup, C.; Kollenz, G. (Tetrahedron, 2004)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)

(untitled) - Haberz, P.; Belaj, F.; Gloe, K.; Wentrup, C.; Kollenz, G. (Supramol. Chem., 2012)